Perceived Loneliness, Peer, and Parental Relationship With Smoking: A Cross-Sectional Analysis of Adolescents Across South-East Asia. (November 2022) - McClure-Thomas, Caitlin; Lim, Carmen; Sebayang, Susy; Fausiah, Fitri; Gouda, Hebe; Leung, Janni
Tobacco use among youth in the South-East Asian region is quite prevalent. This study aims to examine if psychosocial factors (perceived loneliness, peer, and parental relationships) were associated with adolescent smoking, and whether the effects were different according to sex and age. Data came from the Global School-based Student Health Surveys collected between 2012 and 2015 in Brunei, Cambodia, Indonesia, Laos, Malaysia, Philippines, Thailand, Timor-Leste, and Vietnam. 64 578 (males = 48.5%) adolescents aged 13-18 completed the survey. Prevalence of past-month cigarette use was 10.6%. Adolescent smoking was associated with loneliness (OR = 1.75), lack of close friends (OR = 1.43), and lack of parental understanding (OR = 1.35). There was significant interactions between sex with loneliness, close friends, and parental understanding ( p < .001). Interactions indicated having no close friends is associated with smoking and is stronger for females than males. Conversely, loneliness was associated with smoking more strongly in males than females. Results indicate that psychosocial factors are linked to adolescent smoking in South-East Asia, suggesting a further need for research on the relation of psychosocial factors with smoking, and their underlying factors.